Assessment Of Fungi In Indoor Daycare Environment. - Nurul Nabilah, Yusof (2025)
Daycare centers play a crucial role in the early development of children, providing essential social and educational experiences. However, indoor environments can harbor various microorganisms, including fungi, which may pose potential health risks to occupants. This study is mainly focus in identifying the fungi concentrations in indoor environment of daycare centers in Kuantan, Pahang. Besides, the other aims of study were to identify the species of airborne fungi in three dayacare centers. The selection of the daycare centers were based on three locations which are residential area, coastal area, and commercial area. To collect the samples, passive sampling was performed and followed NMAM 0800 method. The sampling was done in a main activity room only for each daycare centers for four slots by putting the equipment at the three different level of breathing zones which are at ground (0 meter), 1.5 meters, and 1.2 meters. The air temperature, relative humidity (RH), and air movement were measured by using Anemometer. Additionally, the fungi species in daycare centers were identified by using Scanning Electron Microscopy (SEM). The result obtained reveals that through the Kruskal-Wallis test, results with the p-value less than 0.05 show that there was significant differences between location of DCC and fungi concentration where DCC C located in commercial area has significantly higher fungi concentration. Besides, there was also significant differences (p<0.05) between slot and fungi concentration where the highest fungi concentration was at slot 2 during the active activity of children. However, there was no significant differences (p>0.05) between breathing zone levels and fungi concentration. Through the Mann- Whitney test, there was no significant differences (p>0.05) of fungi concentration between natural and mechanical ventilation for three daycare centers. Besides, result obtained through Spearman’s Correlation Coefficient test, it reveals that there is significant and negative correlation between occupant’s density and fungi concentration (r = -0.454, p<0.05). However, there is no significant and negative correlation between climate indoor factors (air temperature, RH, air movement) and fungi concentration. Lastly, in this study, there were three species of fungi successfully identified in three daycare centers which are Aspergillus sp., Mucor sp., and Penicillium sp. Overall findings of this study indicate that daycare centers in Kuantan, Pahang, exhibit varying levels of fungal contamination. While location and activity levels significantly influence fungal concentrations, factors like ventilation type and indoor climate parameters did not show a significant correlation. The identification of common fungal genera such as Aspergillus, Mucor, and Penicillium highlights the need for further investigation into their potential health implications for children and staff.